2021
DOI: 10.1093/ajcp/aqaa259
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Section Quality Assurance

Abstract: Objectives Composite frozen section turnaround time has limited value, precluding assessment of certain processes: slide preparation (technical) and diagnosis (interpretation). We examined whether measuring these elements could identify delays, hypothesizing that longer times were related to (1) inefficient technical processes and (2) case-specific diagnostic challenges.. Methods Technical and interpretive times were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…A large single‐institution study reported that the current average turnaround time for delivering intraoperative head and neck frozen section results is 19.7 min 18 . However, a majority of the frozen section procedures used to produce these findings were conducted on small specimens that required minimal grossing.…”
Section: Discussionmentioning
confidence: 99%
“…A large single‐institution study reported that the current average turnaround time for delivering intraoperative head and neck frozen section results is 19.7 min 18 . However, a majority of the frozen section procedures used to produce these findings were conducted on small specimens that required minimal grossing.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria comprised: (1) Suspected tumor lesions of the central nervous system, (2) aged over 18 years, and (3) the patient is willing and able to give informed consent for participation. Exclusion criteria comprised: (1) Patient does not agree to participate in the study or (2) unable to or unwilling to give informed consent. Specimen samples were excluded if the collected specimen was inadequate, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid intraoperative histopathological analysis of fresh frozen tumor tissue is an essential tool for biopsy and surgical resection control [ 1 ]. This is based on a time-consuming and costly intraoperative pathology workflow for intraoperative decision-making that often leads to prolonged surgery times with the patient kept in anesthesia waiting for the pathological diagnosis [ 2 , 3 ]. In addition, not every hospital providing surgeries in patients with brain tumors holds a (neuro)pathology unit available for rapid fresh frozen diagnostics and even if, it is usually only available during normal working hours.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the combination of antibodies used in all cases, pathologists can still draw correct conclusions through a comprehensive evaluation of the positive and negative aspects of other antibodies. The FS turnaround time is considered an important indicator, 22 so RIHC turnaround time must be completed as quickly as possible. Considering that increasing the number of antibody items extends the time required for section preparation, it is recommended to use fewer than 6 antibodies in the panel.…”
Section: Discussionmentioning
confidence: 99%